Preferential MBE Growth and Characterization of SiGe Nanoislands on Depth-Selective Si Pits Etched by Ar+ Plasma - Seker, Isa; Karatutlu, Ali; Istengir, Sumeyra (WILEY-V C H VERLAG GMBH, 2018)
In this study, the size selective deposition of SiGe nanoislands is demonstrated to be possible only in Si nanopits using a molecular beam epitaxy (MBE) system. The depth of the etched Si substrate prepared by Ar+ plasma etching just before the deposition seems to be playing a role in the selectivity of keeping the SiGe nanoislands only inside the nanopits. We observed that, when the thickness of the deposited SiGe layer is around the mean pit depth, which is 4nm in this case, Ge nucleation takes place selectively on the pre-etched pits. Relatively larger deposition thickness (e.g., 40nm) is demonstrated to suppress the preferential growth of the Ge nanocrystals (NCs)/Si NCs which are in return observed all along the surface of the Si substrate. On the other hand, surface migration is considered to play a role in very small depth (relatively more shallow pits) and yielding the unfilled Si nanopits (ca. 1.5nm) whereas Ge NCs selectively nucleate only within those having larger depths (ca. 3nm). Such site-specific 3D controlled growth of nanoislands is shown for the deposition of different semiconductor nanocrystals on top of another for formation of nanodevices fabricated in a single nanopit.
Keywords: dry etch; molecular beam epitaxy; selective growth; SiGe nanoislands; surface migration; GERMANIUM QUANTUM DOTS; SILICON; RAMAN; SHAPE; Materials Science; Physics